Fairy 'Mouse Deer And Snail' In Developing Value Education Character In Learning Mathematics - Nur Indah Sari; Eka Septiani; Arif Rahman Hakim (ISEJ : Indonesian Science Education Journal, 2021)
Folklore can be used as one tool to deliver a range of values of character education, as well as to Strengthen the development of national identity in the younger generation of Indonesia. Value of character education can be built up through folklore in each subject in formal education, Including the teaching of mathematics. Implemented a learning Mathematics always aim to build a variety of capabilities, both in the form of hard skills and soft skills mathematic mathematic. Folklore that are Discussed in this article is the Fabled 'hare and Snail'. Use of the Fabled 'hare and Snail' conceptually in this article is Aimed at transforming diverse moral message that characterizes the value of character education, roomates would Become an important part regarding the goals of learning activities in the form of mathematicsmathematical power, Such as problem-solving ability and a positive attitude towards math, Articles are arranged in this qualitative descriptive intended to Convey a moral message contained in the fable 'hare and Snail'. Results can be Achieved on this article items, namely through the Fabled 'hare and Snail' is sung in the learning of mathematics, is expected to instill a maximum of mathematical problem solving ability, capable of up to foster a positive attitude towards math, and so forth. Overall, it can be concluded that the folklore must continue to be preserved, and can be formally brought in all the learning activities in the classroom, in order to foster the educational value of the character of the Indonesian nation.